Sikap Bangga Menggunakan Bahasa Indonesia dalam Komunikasi Sehari-Hari - Aini Syarah; Ratu Azizah Maulani Hasan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The proud attitude of using Indonesian in daily communication is a manifestation of awareness of national identity and the importance of language as a unifying tool. In the context of globalization, Indonesian not only functions as a symbol of pride and nationalism, but also reflects the identity of a nation that is rich in cultural and linguistic diversity. As the country's official language, Indonesian has a significant role in building national unity and identity, as well as respecting existing cultural heritage. Apart from that, there are challenges and problems that can hinder the development of an attitude of being proud to speak Indonesian, such as education and differences in attitudes in various groups based on age and social background. Therefore, it is important to identify driving factors that can increase public awareness and understand existing social dynamics. Thus, this research uses a qualitative descriptive method, this research is very suitable for discussing the proud attitude of using Indonesian in everyday communication, because it can explore the nuances and complexities that exist behind this phenomenon. This research can also contribute to the development of linguistic and social theories related to identity, culture and communication. The research results can be used to enrich the literature on the relationship between language and national identity.